Therapeutic resources used by physiotherapists for the relief of labor pain: a cross-sectional study - Alessandra de Campos Gonçalves; Giovana Garçoni Poli; Clara Maria de Araujo Silva; Ana Carolina Sartorato Beleza; Richard Eloin Liebano (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective The aim of the study was to identify non-pharmacological therapeutic resources used by physiotherapists for pain relief during labor and childbirth. Methods This is a cross-sectional study conducted from January to March 2021, followed the STROBE guidelines. It included Brazilian physiotherapists with a minimum of two years in obstetric care experience. Data were collected using a 33-item online questionnaire, which covered sociodemographic details and the utilization of non-pharmacological resources. Descriptive analysis was used to determine participant characteristics. Associations between sociodemographic variables, specialist titles, participation in scientific events, and methods for pain relief methods during childbirth were assessed using chi-square or Fisher’s exact tests. Data were analyzed using SPSS version 23.0, with a significance level set at 5% (p < 0.05). Results A total of 114 Brazilian physiotherapists participated in this study. Participants chose to utilize non-pharmacological therapies and resources that are within the scope of physiotherapists’ practice for labor pain. Kinesiotherapy with the use of devices was the most employed technique for pain relief during the birthing process. Conclusion The study highlights the prevalent use of non-pharmacological therapeutic resources, particularly kinesiotherapy with devices, among Brazilian physiotherapists for labor pain relief.